Multi-temporal 3D point cloud-based quantification and analysis of geomorphological activity at an alpine rock glacier using airborne and terrestrial LiDAR - Zahs, Vivien; Hämmerle, Martin; Anders, Katharina; Hecht, Stefan; Sailer, Rudolf; Rutzinger, Martin; Williams, Jack G.; Höfle, Bernhard (Permafrost and periglacial processes, 2019)
Change analysis of rock glaciers is crucial to analyzing the adaptation of surface and subsurface processes to changing environmental conditions at different timescales because rock glaciers are considered as potentially unstable slopes and solid water reservoirs. To quantify surface change in complex surface topographies with varying surface orientation and roughness, a full three-dimensional (3D) change analysis is required. This study therefore proposes a novel approach for accurate 3D point cloud-based quantification and analysis of geomorphological activity on rock glaciers. It is applied to the lower tongue area of the Äußeres Hochebenkar rock glacier, Ötztal Alps, Austria. Multi-temporal and multi-source topographic LiDAR data are used to quantify surface changes and to reveal their spatial and temporal characteristics at different timescales within the period 2006-2018. LiDAR-based examinations are complemented with subsurface characteristics obtained from electrical resistivity tomography. This combined approach reveals active and variable spatial and temporal surface dynamics in the investigated area, with minimum detectable change between 0.09 and 0.65 m at 95% confidence. Given that this approach overcomes current uncertainties in established methods of differentiating complex rock glacier surfaces, we consider it a valuable addition that can be applied to objects of similar properties such as landslides or glaciers.
Online veröffentlicht: 11. Juli 2019
Gesehen am 29.07.2024